2006
DOI: 10.1111/j.1365-2958.2006.05101.x
|View full text |Cite
|
Sign up to set email alerts
|

Bradyrhizobium japonicum senses iron through the status of haem to regulate iron homeostasis and metabolism

Abstract: SummaryThe Irr protein from the bacterium Bradyrhizobium japonicum is expressed under iron limitation to mediate iron control of haem biosynthesis. The regulatory input to Irr is the status of haem and its precursors iron and protoporphyrin at the site of haem synthesis. Here, we show that Irr controls the expression of iron transport genes and many other iron-regulated genes not directly involved in haem synthesis. Irr is both a positive and negative effector of gene expression, and in at least some cases the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
149
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(158 citation statements)
references
References 40 publications
6
149
0
3
Order By: Relevance
“…This reciprocal regulation via Irr and RirA allows A. tumefaciens to accumulate sufficient cellular iron pools and grow efficiently under iron-limited conditions. The irr-null mutant cannot mount the proper low-iron regulatory response, resulting in a decreased cellular iron pool similar to the decrease in total iron content observed in B. japonicum, as well as a dramatic growth yield defect (74). This is presumably through a combination of unregulated consumption of iron and the limited expression of iron uptake systems.…”
Section: Discussionmentioning
confidence: 96%
“…This reciprocal regulation via Irr and RirA allows A. tumefaciens to accumulate sufficient cellular iron pools and grow efficiently under iron-limited conditions. The irr-null mutant cannot mount the proper low-iron regulatory response, resulting in a decreased cellular iron pool similar to the decrease in total iron content observed in B. japonicum, as well as a dramatic growth yield defect (74). This is presumably through a combination of unregulated consumption of iron and the limited expression of iron uptake systems.…”
Section: Discussionmentioning
confidence: 96%
“…To further address the effects of manganese on iron metabolism, we examined the expression of several genes known to be regulated by iron at the mRNA level in B. japonicum wild-type cells. blr3555 and bll4920 encode iron siderophore transport outer-membrane receptors, and blr6519 encodes an iron-independent fumarase, which replaces the iron-sulfur fumarase when the metal is limiting (15,17,25). Cells were grown under various iron or manganese conditions, and mRNA encoding each gene was examined by quantitative realtime PCR (qPCR).…”
Section: Resultsmentioning
confidence: 99%
“…The Irr protein is a global iron regulator in B. japonicum (14,15). Most genes that are strongly regulated by iron are directly or indirectly controlled by Irr (14,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of function mutations in the IRR gene are sufficient to uncouple heme synthesis from iron availability, resulting in porphyrin accumulation and cytotoxicity [21,42,45]. Notably, recent findings indicate that in B. japonicum, IRR allows the sensing of iron level via heme synthesis to regulate iron homeostasis and metabolism [49]. In addition, it was also shown that IRR plays a role in mediating the control of heme synthesis in response to oxidative stress [50].…”
Section: Irr Coordinates Heme Synthesis Under Iron Limitation In B Jmentioning
confidence: 99%